A Phase 1 study of the safety, pharmacokinetics and anti-leukemic activity of the anti-CD123 monoclonal antibody CSL360 in relapsed, refractory or high-risk acute myeloid leukemia. Issue 5 (May 2015) - He, Simon Z.; Busfield, Samantha; Ritchie, David S.; Hertzberg, Mark S.; Durrant, Simon; Lewis, Ian D.; Marlton, Paula; McLachlan, Andrew J.; Kerridge, Ian; Bradstock, Kenneth F.; Kennedy, Glen; Boyd, Andrew W.; et al.
Abstract Acute myeloid leukemia (AML) blasts express high levels of interlekin-3 (IL-3) receptor-α (CD123). CSL360 is a recombinant, chimeric immunoglobulin G1 (IgG1), anti-CD123 monoclonal antibody (MoAb) that neutralizes IL-3 and demonstrates anti-leukemic activity in vitro. This phase 1 study assessed safety, pharmacokinetics and bioactivity of weekly intravenous CSL360 for 12 weeks in 40 patients with advanced AML across five dose levels (0.1–10.0 mg/kg). Other than mild infusion reactions, CSL360 was well tolerated. The maximal tolerated dose was not reached. The half-life was 4.9 days, and the area under the curve (AUC) and maximum concentration (Cmax) increased proportionally with dose. Doses ≥ 3.0 mg/kg resulted in complete saturation and down-regulation of CD123 and abolition of ex vivo proliferative responsiveness to IL-3, indicating adequate blockade of IL-3 signaling. Two patients responded, with one remaining in complete remission after 17 doses. CSL360 bound CD123 specifically, but did not induce anti-leukemic activity in most patients. While safe, MoAb blockade of CD123 function is insufficient as a therapeutic strategy.